A prospective phase II study of prostate-specific antigen-guided salvage radiotherapy and 68Ga-PSMA-PET for biochemical relapse after radical prostatectomy – The PROPER 1 trial. (September 2022) - Gunnlaugsson, Adalsteinn; Johannesson, Vilberg; Wieslander, Elinore; Brun, Eva; Bitzén, Ulrika; Ståhl, Olof; Bratt, Ola; Ahlgren, Göran; Ohlsson, Tomas; Kjellén, Elisabeth; Nilsson, Per
Highlights: PSA response during the first weeks of salvage radiotherapy (SRT) of prostate cancer is highly predictive for tumour control. PSA responders received conventional local SRT towards the prostate bed while the treatment plan of PSA non-responders was changed after 5 weeks of SRT to also include pelvic lymph nodes/metastases. High tumour control rate with moderate side effects were observed in both PSA responders and non-responders with this new personalised treatment concept. It is now further investigated in a prospective phase III trial (NCT04858880). Abstract: Background and purpose: The treatment of biochemical recurrence (BCR) after prostatectomy is challenging as the site of the recurrence is often undetectable. Our aim was to test a personalised treatment concept for BCR based on PSA kinetics during salvage radiotherapy (SRT) combined with prostate-specific membrane antigen positron emission tomography (PSMA-PET). Materials and methods: This phase II trial included 100 patients with BCR. PSMA-PET was performed at baseline. PSA was measured weekly during SRT. Initially, 70 Gy in 35 fractions was prescribed to the prostate bed. Radiotherapy was adapted after 50 Gy. Non-responders (PSA still ≥ 0.15 ng/mL) received sequential lymph node irradiation with a boost to PSMA-PET positive lesions, while responders (PSA < 0.15 ng/mL) continued SRT as planned. PET-findings were only taken into consideration for treatment planning in case of PSA non-response after 50 Gy. Results: Data from 97 patients were eligible for analysis. Thirty-four patients were classified as responders and 63 as non-responders. PSMA-PET was positive in 3 patients (9%) in the responder group and in 22 (35%) in the non-responder group (p = 0.007). The three-year failure-free survival was 94% for responders and 68% for non-responders (median follow-up 38 months). There were no significant differences in physician-reported urinary and bowel toxicity. Patient-reported diarrhoea at end of SRT was more common among non-responders. Conclusion: This new personalised treatment concept with intensified SRT based on PSA response demonstrated a high tumour control rate in both responders and non-responders. These results suggest a clinically significant effect with moderate side effects in a patient group with otherwise poor prognosis. PSMA-PET added limited value. The treatment approach is now being evaluated in a phase III trial. Clinical trial registration numbers: NCT02699424&ISRCTN45905321.